A COMPARATIVE STUDY ON THE POPULATION AND HABITATS OF THE GREY FRANCOLIN FRANCOLINUS PONDICERIANUS AND BLACK FRANCOLIN FRANCOLINUS FRANCOLINUS IN MANG GAME RESERVE, HARIPUR, PAKISTAN - M. F. Khan; M. S. Awan; A. Q. Nayyer; K. Mehmood; M. N. K. Khattak (Journal of Animal and Plant Sciences, 2015)
Grey and black francolins are the prime game birds of Pakistan. According to Red Data Book both species are declared as threatened worldwide. However in Pakistan the status of both species is not assessed. Therefore to study population and habitat of both the species is of critical importance. The current study was conducted in Mang game reserve, Haripur in order to explore the comparative population and habitat structure of both the species. For population dynamics, the data were collected fortnightly and calculated month wise for a year in the three sub habitats of the game reserve. Our study reveals that in grassland the population density of grey francolin ranged from 0.63±0.00/Km2 in January to 4.69±2.2/Km2 in the month of October. In hilly land the population of grey francolin ranged from 1.9±0.00/Km2 in January to 6.3±0.00/Km2 in October and in wetland land the population of grey francolin ranged from 1.75±1.06/Km2 in January to 4.93±2.72/Km2 in October. The population of black francolin in grassland ranged from 0.63±0.00/Km2 in July to 2.19±1.32/Km2 and 2.19±0.45/Km2 in October and November respectively. In hilly land the population of black francolin ranged from 1.6±0.42/Km2 in March and June to 4.40±0.85/Km2 in October. The same way in wetland the black francolin’s population ranged from 0.98±0.46/Km2 in February to 3.75±0.92/Km2 in October and November. The dominant plants in all the three habitats were Acacia Modesta and Cyndondactylon. The major threats to the francolins included illegal hunting, overgrazing and use of pesticides in the crop fields. Mang game reserve can prove to be suitable place for conservation of both the francolins.
Keywords: Grey francolin; Black francolin; Population; Density; Habitat; Pakistan